Inulin type fructans - functional food ingredients - Roberfroid, Marcel B. (CRC Press LLC, 2011)
Inulin and oligofructose are naturally occurring resistant carbohydrates that have a variety of uses as functional food ingredients. In addition to their role as prebiotics that selectively stimulate the growth of beneficial bacteria in the intestines, these inulin-type fructans act as dietary fiber in the digestive system and have applications as a sugar substitute and fat replacer.